Negative role of oxidised polyphenols and reductones in beer - Savel, Jan (BrewingScience, 2006)
The oxidation-reduction reactions of the oxidised pyrogallol as an example of oxidised polyphenol with ascorbic acid were studied using methylene blue reoxidation reaction. This technique uses methylene blue photobleaching followed by its colourless leucoform reoxidation. Oxidation activity of oxidised pyrogallol increased with the time of pyrogallol oxidation. Polyphenols can act as an carrier of oxygen to reductones which is associated with the formation of degradation products accelerating electron exchange. The illumination also accelerated the redox reaction between polyphenols and reductones providing various radical and non-radical oxidation species. Beer ageing comprises polyphenol or reductone oxidation providing reactive species under aerobic or anaerobic condition.